Impact of Mining Exports and Production on the Economic Growth of the Apurimac Region in 2004-2016 - Andrés Zavala, Abel (2023)
This study analyzes the impact of mining and agricultural exports on the economic development of the Apurimac region during the period of 2004-2016. It also studies the organization of the region in the period 2004-2016 where agriculturally, potato production is notable, as well as tourism and the mining sector’s production from Las Bambas. The Las Bambas mining megaproject (Las Bambas), which started production in 2016, exports copper and non-traditional products such as coffee and avocado, resulting in a significant change in the economic and financial landscape of Apurimac. The analysis focuses on the economic activity of multiple banking and microfinance companies (including deposits and credits) as well as the region’s overall economic development. Additionally, the study examines the Human Development Index (HDI) of two impoverished provinces located within Las Bambas: Grau, with an HDI of 0.2425, and Cochabambas, with an HDI of 0.2193. Following the start of copper export (2010-2015), the region experienced an economic growth rate of 8.4%, surpassing the national economy’s growth rate of 5.4%. In 2016, as a result of the development of Las Bambas project, the region witnessed a remarkable 141.5% increase in its economy.